Cardiac sarcoidosis and coronary artery disease: a two-hit mechanism to left ventricular dysfunction (Or is It)? - Hansen, J. C.; Patel, A. R.; Nayak, H. N.; Moss, J. D.; Sweiss, N.; Beshai, J. F. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2013)
This report describes a case of cardiac sarcoidosis in a 40-year-old man with minimal risk factors for coronary artery disease who was found to have a critical coronary lesion on angiography performed for declining left ventricular function. The case highlights the diagnostic and therapeutic issues surrounding cardiac sarcoidosis and raises the question of a possible link between sarcoidosis and premature coronary artery disease. It also stresses the importance of ruling out ischemia in any patient with declining left ventricular function.